2014
DOI: 10.1128/iai.02213-14
|View full text |Cite
|
Sign up to set email alerts
|

DAP1, a Negative Regulator of Autophagy, Controls SubAB-Mediated Apoptosis and Autophagy

Abstract: c Autophagy and apoptosis play critical roles in cellular homeostasis and survival. Subtilase cytotoxin (SubAB), produced by non-O157 type Shiga-toxigenic Escherichia coli (STEC), is an important virulence factor in disease. SubAB, a protease, cleaves a specific site on the endoplasmic reticulum (ER) chaperone protein BiP/GRP78, leading to ER stress, and induces apoptosis. Here we report that in HeLa cells, activation of a PERK (RNA-dependent protein kinase [PKR]-like ER kinase)-eIF2␣ (␣ subunit of eukaryotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…This effect also was observed when much lower concentrations of SubA 1 were delivered into cells via the SubB 1 transport subunit, and comparable results were reported earlier by other groups for the SubAB 1 cytotoxin (37)(38)(39)(40). This finding explains the observed alterations in cell morphology and the reduced number of viable cells after incubation with high concentrations of SubA 1 in the absence of SubB 1 .…”
Section: Discussionsupporting
confidence: 78%
“…This effect also was observed when much lower concentrations of SubA 1 were delivered into cells via the SubB 1 transport subunit, and comparable results were reported earlier by other groups for the SubAB 1 cytotoxin (37)(38)(39)(40). This finding explains the observed alterations in cell morphology and the reduced number of viable cells after incubation with high concentrations of SubA 1 in the absence of SubB 1 .…”
Section: Discussionsupporting
confidence: 78%
“…Despite analyses of several aspects of the biochemical processes involved in the functionality of SubAB and its consequences on the target cells, aspects of the regulation of SubAB expression itself are still unvetted [ 135 , 136 ]. One hypothesis is that the expression is triggered based on the position in the genome.…”
Section: Toxins Of Lee-negative Stecmentioning
confidence: 99%
“…Furthermore, Halder et al reported that the Helicobacter pylori produced HP0175, a peptidyl-prolyl cis-trans isomerase, activates the PERK arm consequently leading to production of ATF4 and CHOP which both induce the expression of autophagy-related genes [ 23 ]. In contrast, SubAB-triggered PERK activation suppresses autophagy [ 24 ]. Thus, PERK-dependent autophagy induction seems to be insult dependent.…”
Section: The Role Of Individual Er Stress Marker Activationmentioning
confidence: 99%